PELAKSANAAN PEMBELAJARAN SENI BUDAYA BERDASARKAN KURIKULUM 2013 REVISI DI SMP NEGERI 31 PADANG - Anggi Musfira; Tulus Handra Kadir; Esy Maestro (SENDRATASIK UNP, 2018)
Abstract This article aims to discover and describe the implementation of learning the art of teaching material specifically cultural art music based on 2013 Revised Curriculum in junior high Country 31 field. Research is descriptive using the approach the qualitative method. The object in this research is the implementation of learning art and culture based on Curriculum Revision in 2013 31 Country Junior High School field. The main instrument in this research is its own researchers and researchers assisted with the supporting instruments be stationery, tools to record in the form of audio and camera. Data collection is carried out by means of observation, interview, documentation and study of the literature. Data analysis was performed on the primary data and secondary data and the data analyzed is done by means of identifying, classifying, analyzing and describing data. The results showed that the implementation of the process of learning the curriculum revision in 2013 learning cultural arts (music) on SMP N 31 the field has not been fully implemented in accordance with the dimensions and direction of 2013 Curriculum revision. In teaching the teacher always wear methods lectures and cooperative, but teachers have received training and knowledge about 2013 Curriculum revision. Conceptually, the teacher is quite understood the concept of Curriculum revision 2013, but still found the discrepancy in the implementation, so haven't been able to achieve learning objectives among other methods, the implementation of 5 m, the allocation of time spent, and the writing of the RPP. Keywords: implementation, cultural arts, curriculum Revision 2013